Implementasi Desain Visual pada Game Puzle “Elephant in Rescue” - Elyzabeth Cipra Manurung; Rinawati Ciptaningrum (Syntax Literate, 2026)
Elephant in Rescue is a casual puzzle genre game. The problems in the game that raise the implementation of visual design include; characters, environments, and user interfaces. In the visual design process, theories and references related to problems are formulated This game consists of three levels, each of which has three stages. Each stage has a different arrangement of obstacles in its environment. The purpose of designing this game is as a medium of entertainment and information about saving elephants to the community with inspiration in the Sumatran Elephant conservation area in Way Kambas National Park, Lampung. This game consists of three levels, each with three stages. Each stage has a different arrangement of obstacles to the environment. The visual problems in the game Elephant in Resque focus on design; characters, environments, and user interfaces. The first part of the visual problem introduces the player when starting to the game. The use of effective and efficient visual design refers to user experience analysis. Visual design in the game aims to be a means of visual communication in game interaction. In addition to being a game entertainment medium and can function as an educational message conveyor about the preservation of Sumatran Elephants in Way Kambas National Park.